Edukasi Kesehatan Dalam Keperawatan Keluarga Tentang Hipertensi Dalam Pemberian Diet Rendah Garam Pada Lanjut Usia (Lansia) Di Puskesmas Martimbang Pematangsiantar - Riska Wani Eka Putri Perangin-angin; Shanty Maria Lissanora Fernanda; Norong Perangin-angin; Azis Mangara (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Hypertension occurs in the age group 31-44 years (31.6%), age 45-54 years (45.3%), age 55-64 years (55.2%). Of the prevalence of hypertension of 34.1%, it is known that 8.8% were diagnosed with hypertension and 13.3% of people diagnosed with hypertension did not take medication and 32.3% did not take medication regularly. This shows that most people with hypertension do not know that they have hypertension so they do not take regular medication now. Various studies have suggested that regular dietary patterns can reduce symptoms of hypertension on a regular basis and can carry out activities properly so that the elderly do not feel burdened in dealing with the disease they are experiencing. The objectives achieved are to provide understanding, understanding and provide health education in hypertension and to increase understanding in treatment regarding low-salt diet patterns and invite the community, especially the elderly around the Health Center of Martangan Pematangsiantar. There has been an increase in the knowledge or understanding of the community at the Martanding Pematangsiantar Health Center regarding various hypertension problems.